2019
DOI: 10.1177/1352458519876037
|View full text |Cite|
|
Sign up to set email alerts
|

No association between cortical lesions and leptomeningeal enhancement on 7-Tesla MRI in multiple sclerosis

Abstract: Background: Autopsy data suggest a causative link between meningeal inflammation and cortical lesions (CLs) in multiple sclerosis (MS). Objective: To use leptomeningeal enhancement (LME) and CLs on 7-Tesla (7T) magnetic resonance imaging (MRI) to investigate associations between meningeal inflammation and cortical pathology. Methods: Forty-one participants with MS underwent 7T MRI of the brain. CLs and foci of LME were quantified. Results: All MS participants had CLs; 27 (65.8%) had >1 focus of LME. Except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 39 publications
2
73
1
Order By: Relevance
“…Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection, and human immun...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were performed in cases with ischemic stroke, transient ischemic attack (TIA), and/or intracerebral hemorrhage (ICH) (n = 20) ( Villringer, 2017 , Ostwaldt, 2015 , Ostwaldt, 2014 , Warach and Latour, 2004 , Latour et al, 2004 , Choi, 2017 , Dechambre, 2000 , Forster et al, 2016 , Gupta, 2017 , Henning et al, 2008 , Hjort, 2008 , Kim, 2005 , Luby, 2019 , Nadareishvili, 2018 , Lee, 2015 , Lee, 2016 , Lee, 2018 , Rozanski, 2010 , Kidwell et al, 2011 , Jolink, et al, 2019 , Barr, 2010 ). Six studies described patients who underwent cardiovascular or intracranial vascular surgery ( Cho, 2014 , Ogami et al, 2011 , Wilkinson, 2000 , Li, 2018 , Suthiphosuwan et al, 2018 , Merino, 2013 ), nine studies patients with multiple sclerosis (MS) (one of these included stroke cases as a positive control ( Eisele, 2015 ) ( Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 , Harrison, 2017 , Jonas et al, 2018 , Zivadinov, 2017 , Zivadinov, 2018 , Zurawski, 2020 , Ighani, 2020 ), four studies patients with meningitis ( Ahmad et al, 2015 , Alonso, 2015 , Fukuoka, 2010 , Splendiani, 2005 ), two studies reported on memory clinic patients and normal aging ( Freeze, 2017 , Freeze et al, 2019 ), one study on Susac syndrome and MS ( Coulette, 2019 ), one study on familial amyloid polyneuropathy ( Hirai, 2005 ), and one study included a mix of diseases, which were presented as follows: inflammatory and immune-mediated neurologic diseases (neuromyelitis optica spectrum disorder, immune-mediated encephalitis, immune-mediated cerebellar ataxia, systemic inflammatory diseases with white matter MRI abnormalities not suggestive for MS and Susac syndrome), noninflammatory neurologic diseases (small vessel disease, migraine, neurodegenerative diseases, compressive myelopathy), human T-lymphotropic virus (HTLV) infection, and human immun...…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies assessed CSF enhancement in MS, of which six with non-overlapping study samples including 897 cases with a pooled mean age of 44 years ( supplemental table e-2 ) ( Zurawski, 2020 , Ighani, 2020 , Coulette, 2019 , Eisele, 2015 , Absinta, 2015 , Bergsland, 2019 ). The reported prevalence estimates within these studies ranged between 1% and 80%, with a pooled prevalence estimate of 21% (95% CI 19–24).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to notice that the nodular pattern may be a normal variant, considering that it has been found in a great proportion of healthy controls [53]. Contradictory data exists on the relationship between LME and the presence of cortical lesions in MS. A strong relationship between the presence of cortical lesions and LME was evidenced by some authors [49], though these results were not confirmed in other works [54]. In the absence of a direct comparison between 7-T and 3-T scans in the same subjects, it is not possible to state that 7-T MRI has a higher sensitivity for leptomeningeal enhancement detection.…”
Section: Leptomeningeal Enhancementmentioning
confidence: 83%
“…Without the use of an unenhanced image, it is likely that the true prevalence of LME at 3-T may be less than previously reported. LME detection modality also varies widely: some authors used subtraction techniques [54] whereas others did not [49,52]. In conclusion, further work is necessary in order to investigate the real prevalence and relevance of LME in MS and to elucidate the ideal MRI protocol to image meningeal inflammation.…”
Section: Leptomeningeal Enhancementmentioning
confidence: 99%
“…In 2 recent 7T studies on RRMS patients, leptomeningeal enhancement was associated with cortical lesion burden 30 or cortical atrophy. 31 Leptomeningeal enhancement is also not MS-specific, being frequent in other inflammatory CNS diseases. 32 Using high-and ultrahigh-field scanners, quantitative MRI techniques improved the evaluation of cortical lesions.…”
Section: Gm Lesionsmentioning
confidence: 99%